The impact of T2T therapy on the treatment of the patients with the early rheumatoid arthritis (data from OREL registry) - V. V. Rybakova; A. S. Avdeeva; D. A. Dibrov; E. L. Nasonov (Научно-практическая ревматология)
Aim – to analyze long-term results of intensive treatment initiated at rheumatoid arthritis (RA) onset in real clinical practice.Material and methods. 93 RA patients were included. Subcutaneous MTX was initiated at 10–15 mg per week with further dose escalation up to 20–30 mg per week. If MTX monotherapy did not allow to achieve treatment target of remission or low disease activity, biologics were added.Results. Against the background of observation, there was a significant decrease in the activity of diseases and the level of acute phase indicators, after 12 months of treatment, the values of the DAS28-ESR indices were 2.76 [2; 3.7], SDAI – 5.34 [1.8; 9.7], CDAI – 5 [1.5; 9.5], corresponded to low disease activity; remission was achieved in 48.6%, low activity – in 17.5%, moderate activity remained in 31%, high activity – in 2.7% of patients. After 6 years the median age of patients was 58 [49; 66] years, the disease duration – 84 [79; 89] months, the low disease activity was documented in 21.3%, and remission – in 7.8% of patients. After 6 years, the value of the activity indices was: DAS28 – 4 [3.4; 4.59], SDAI – 15.06 [9.32; 21], CDAI – 15 [9; 21]; remission – in 7.7%, low disease activity – in 21.1%, moderate activity – in 60%, high activity – in 11.1% of patients.Conclusion. Intensive therapy initiated at RA onset demonstrates high effectiveness, allowing to achieve remission/low disease activity in about 30% of patients. Adherence to this strategy allowed to discontinue biologics in and synthetic DMARDs after achieving treatment target.